2012
DOI: 10.5194/bg-9-4421-2012
|View full text |Cite
|
Sign up to set email alerts
|

The benthic foraminiferal community in a naturally CO<sub>2</sub>-rich coastal habitat of the southwestern Baltic Sea

Abstract: Abstract. It is expected that the calcification of foraminifera will be negatively affected by the ongoing acidification of the oceans. Compared to the open oceans, these organisms are subjected to much more adverse carbonate system conditions in coastal and estuarine environments such as the southwestern Baltic Sea, where benthic foraminifera are abundant. This study documents the seasonal changes of carbonate chemistry and the ensuing response of the foraminiferal community with bi-monthly resolution in Flen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…perturbations that are expected through air-sea CO 2 uptake in the average surface ocean in the next 100 years (Cao & Caldeira, 2008;Borges & Gypens, 2010;Haynert et al, 2012). The observed fluctuations in seawater pCO 2 over the seasonal cycle directly translate into changes in mussel haemolymph pCO 2 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…perturbations that are expected through air-sea CO 2 uptake in the average surface ocean in the next 100 years (Cao & Caldeira, 2008;Borges & Gypens, 2010;Haynert et al, 2012). The observed fluctuations in seawater pCO 2 over the seasonal cycle directly translate into changes in mussel haemolymph pCO 2 .…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to the open ocean, where seawater pCO 2 is close to atmospheric values, pCO 2 in coastal habitats is much more variable (Feely et al, 2010;Cai et al, 2011;Melzner et al, 2012;Hofmann et al, 2011). Shallow temperate estuaries such as the Western Baltic Sea, with a strong seasonal vertical stratification due to salinity and temperature gradients are characterized by higher and more fluctuating seawater pCO 2 Melzner et al, 2012, Haynert et al, 2012. In these areas, community respiration leads to decreases in pO 2 and increases in pCO 2 below the thermocline.…”
Section: Introductionmentioning
confidence: 99%
“…The latter displayed the weakest response towards eCO 2 in the long term, but the highest increase in short-term response of NP at eCO 2 in the gas exchange cuvette, suggesting an overall low expression of HCO 3 receptors. In their natural benthic environment, elevated CO 2 of up to 3000 µatm can occur due to high organic matter decomposition and remineralisation (Haynert et al, 2012). The capability to swiftly downregulate the CCM is an important prerequisite for attaining high CO 2 tolerance in this environment.…”
Section: Differences Between Cyanobacterial Speciesmentioning
confidence: 99%
“…To date, no ocean acidification studies were reported to pursue culturing experiments with benthic foraminifera in their natural sedimentary environment. The field study of Haynert et al (2012) in Flensburg Fjord exhibited that the carbonate chemistry of sediment pore water differed strongly from the conditions in the overlying near-bottom water. Sediment pore water pCO 2 was constantly high, ranging from 1244 to 3324 µatm during the entire year.…”
Section: Introductionmentioning
confidence: 99%